Pancasila as a Paradigm of Science and Technology - Nanda Putri Amelia; Intan Sabila; Masduki Asbari (AGUSPATI RESEARCH INSTITUTA, 2022)
This paper aims to determine the concept of Pancasila in the development of science and technology by using examines Pancasila as a Development Paradigm. Entering the era of the industrial revolution 4.0, the order of life refers to the world of the digital industry, as well as the field of science and technology (IPTEK). Revolution Industry 4.0 requires every individual to run fast to develop technological literacy skills, data, and human resources. These three things become the basic capital in the development of various each individual's competence. The development and progress of science and technology today cannot be separated from mastery of these three literacies The development of science and technology that is not balanced with a fundamental foundation nation, will contribute more negative influence than positive. Misuse of science and technology will threaten the existence of human life in the future. Therefore, a weapon is needed to counteract the negative possibilities of the development of science and technology, one of which is Pancasila. Magic Pancasila is not only limited to being the basis of the state, a way of life, and a unifying force for the Indonesian nation. but also serve as a guiding star in all aspects of life, including the development of science and technology. The basic values ​​contained in Pancasila must be used as the main guidelines in science and technology development. Pancasila is used as the basis for the development of science and technology, which is expected to have an impact broadly on the benefit of the life of the Indonesian nation. Science and technology may develop and advance but must be balanced by maintaining and implementing the noble values ​​of the nation's ideology in all aspects of national and state life.